2022
DOI: 10.1080/10447318.2022.2121052
|View full text |Cite
|
Sign up to set email alerts
|

Can a Video Game with a Fictional Minority Group Decrease Intergroup Biases towards Non-Fictional Minorities? A Social Neuroscience Study

Abstract: A critical scientific and societal challenge consists in developing and evaluating interventions that reduce prejudice towards outgroups. Video games appear to be a promising method but a number of falls in the current scientific literature prevents to fully understand the potential sizeable impact of video games on reducing prejudice. The present study investigated to what extent a video game designed to reduce prejudice towards minorities in a fictional society has the potential to reduce prejudice towards n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 73 publications
(45 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, we investigated the effect of attitude importance on attitude changes. The key study finding, that is, that playing the test video game changed players' attitudes towards the depicted historical events supports the current literature (Cangas et al, 2017; Guillaume & Caspar, 2022; Kampf, 2016a; Mulak & Winiewski, 2022) which claims that video games affect our attitudes towards topics depicted in games. They can, therefore, shape how we think about the topics represented in them.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Furthermore, we investigated the effect of attitude importance on attitude changes. The key study finding, that is, that playing the test video game changed players' attitudes towards the depicted historical events supports the current literature (Cangas et al, 2017; Guillaume & Caspar, 2022; Kampf, 2016a; Mulak & Winiewski, 2022) which claims that video games affect our attitudes towards topics depicted in games. They can, therefore, shape how we think about the topics represented in them.…”
Section: Discussionsupporting
confidence: 83%
“…Several studies have suggested that video games can affect players' attitudes towards the topics that these video games depict. For instance, they can affect attitudes towards prejudice against minorities, as shown in Guillaume and Caspar (2022); attitudes towards food safety, as demonstrated in Quick et al (2013); attitudes towards mental health, as explored in Cangas et al (2017); attitudes towards historical events, as discussed in Kolek et al (2021); and attitudes towards protracted conflicts, as analysed in Kampf (2016a). However, it is important to note that other studies have yielded mixed results or failed to confirm such a video games' effect on attitudes (Barthel, 2013; Peña et al, 2018; Potter et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few studies have tried to verify whether racial prejudices can be reduced, which could be of great relevance to society. In Pech and Caspar [ 107 ] conducted a study to investigate whether a video game designed to reduce prejudice against minorities in a fictional society has the potential to decrease prejudice against minorities in real life as well. A positive effect of the test game compared to the control game on the attenuation of prejudice against an out-group individual was observed.…”
Section: Understanding Racial Bias Through Electroencephalographymentioning
confidence: 99%